Transparansi dan Akuntabilitas Dalam Pengelolaan Keuangan Rumah Sakit Daerah Kalisat Di Masa Pandemi Covid-19 - Merryana Stephanie Hidayat; Oktaviani Ari Wardhaningrum; Andriana Andriana (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The purpose of this research is to analyze how accountability and transparency of financial management at the Kalisat Regional Hospital, East Java during the pandemic of Covid 19. This study used a qualitative approach with a case study method. For purpose collecting the data, we used several techniques such as observation, interviews, and documentation. The implementation of accountability and transparency in financial management during the covid-19 pandemic is in accordance with Government Regulation of the Republic of Indonesia Number 23 of 2005 as last amended by Government Regulation of the Republic of Indonesia Number 74 of 2012. However, the disclosure of financial reports and hospital performance reports has not been freely accessible to the public, so that transparency or disclosing information to the public has not yet been implemented properly.